Environmental Influences on Tobacco Use Among Asian American and Pacific Islander Youth. Issue 5 (September 2013) - Tanjasiri, Sora Park; Lew, Rod; Mouttapa, Michele; Lipton, Rob; Lew, Lillian; Has, Sovanna; Wong, Michelle
There is growing interest in understanding individual and environmental influences on youth risk behaviors, including tobacco use. The purpose of this article is to describe the processes and findings from a study that sought to increase the capacity of Asian American and Pacific Islander (AAPI) community-based organizations to understand and address the environmental influences on tobacco use among AAPI youth. Using a multimethod approach to data collection that included GIS (geographic information system) mapping, Photovoice, and individual youth surveys, a team of community and university researchers conducted a 3-year study to assess and address the environmental influences of tobacco use among youth. Community-based participatory research principles guided the study and facilitated unique capacity building and analyses throughout the study period. Results in Long Beach from all three methods highlighted the associations between youth smoking and environmental factors: GIS mapping identified at least 77 separate locations of pro-tobacco influences, photographs captured many of these locations and provided youth leaders with opportunities to identify how other influences contributed to smoking risk, and surveys of youth indicated that perceived community safety and proximity to pro-tobacco influences were associated with smoking in the past 30 days. Subsequent community-based organization activities undertaken by study partners are also discussed, and lessons learned summarized.